Deuterium retention in W and W-Re alloy irradiated with high energy Fe and W ions: Effects of irradiation temperature. (December 2016) - Hatano, Y.; Ami, K.; Alimov, V.Kh.; Kondo, S.; Hinoki, T.; Toyama, T.; Fukuda, M.; Hasegawa, A.; Sugiyama, K.; Oya, Y.; Oyaidzu, M.; Hayashi, T.
Highlights: Deuterium retention in W after irradiation of high energy Fe ions at 1073 and 1273 K was significantly reduced by Re addition. Effect of Re addition was small after irradiation at lower temperatures. Re addition suppressed growth of vacancy clusters during high temperature irradiation. Significant reduction in D retention by Re addition observed after high temperature irradiation was ascribed to the reduced density of vacancy clusters acting as strong traps against D atoms. Abstract: Neutron irradiation to W induces defects acting as traps against hydrogen isotopes and transmutation elements such as Re and Os. To investigate synergetic effects on radiation-induced defects and Re, deuterium (D) retention in W and W–5% Re samples were examined after irradiation with 6.4 MeV Fe ions at 523–1273 K followed by exposure to D2 gas at 673 K. The value of D retention in W–5% Re was lower than that in W by orders of magnitude after the irradiation at high temperatures (≥1073 K), while no significant effects of Re addition was observed after irradiation at 523 K. Irradiation with 20 MeV W ions at room temperature followed by exposure to D plasma at 443–743 K also resulted in small difference in D retention between W and W–5% Re samples. The results of positron lifetime measurements showed that the reduced D retention by Re observed after high temperature irradiation was due to suppression of formation of vacancy-type defects (monovacancies and vacancy clusters) by Re.